IMPLEMENTASI KOMPETENSI PROFESIONAL GURU MATA PELAJARAN AKIDAH AKHLAK DI MAN 1 KOTA SUKABUMI - Muhamad Ridho, Ziyad; Mustofa, Taufik; Makbul, M (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research explores how Akidah Akhlak (Moral Theology) teachers at MAN 1 Kota Sukabumi implement their profesional competencies, examining the underlying factors and resulting outcomes. Adopting a descriptive qualitative framework, the study drew data from in-depth interviews, observations, dan archival documentation involving teachers, the school principal, and students. Analysis followed Miles and Huberman’s interactive model. The findings reveal a structured approach to profesional competence, characterized by integrated subject mastery, innovative teaching strategies, and the strategic use of digital tools. While progress is bolstered by strong leadership and a vibrant religious culture, teachers still Ade hurdles like administratif burdens and the influence of social media. Ultimately, these efforts have significantly improved students’ character, religious practices, and critical thinking skill.